Microstrip array antenna for automobile radar system - Abdel Rahman Osman, Mai (2006)
Point to point communication brings a crucial responsibility to antennas since they are expected to provide a transmission between those devices. The Industry, Scientific and Medical (ISM) Band, Unlicensed with the range 2.4 - 2.4835 GHz is used as the operation band. In a high performance point to point application where size, weight, cost, performance, ease of installation are constrains, a suitable antenna is very much required. To meet these requirements, microstrip antenna is usually preferred. Microstrip antennas are currently one of the fastest growing segments in the telecommunications industry and promised to become the preferred medium of telecommunication in the future. Although microstrip antenna has several advantages, it also has several drawbacks such as low gain and narrow bandwidth. These disadvantages can be overcome by constructing many patch antennas in array configuration. This project focuses on the design of microstrip patch antenna with operating frequency at 2.45GHz for automobile radar system. The antenna is mainly intended to be used as receiving antenna and receives signals transmitted from an automobile radar system in order to control the movement of the car. An array design based on series fed configuration and consisting of four rectangular patch elements was designed, simulated, fabricated and measured. These elements are connected directly to the microstrip line at their corners and inclined 45 degree in order to achieve circular polarization. The simulation, fabrication and measurement methods were accomplished with the aid of MathCAD, AWR Microwave Office 2004, AutoCAD, FR4 Board, UV Equipment, Macroni Scalar Analyzer 6204 and Anechoic Chamber. The design met the ISM BAND Standard and able to operate in this Band. The fabricated array is found to have a variation in the operating frequency from the simulation resonant frequency. Return loss results of the fabricatd design have a value of -32.8dB with a bandwidth of 4.8%, which could be considered as a narrow band width. This further strengthens the theory of series feed configurations that arrays produce better return loss but narrower bandwidth than that of a single element.